Pesquisa de fatores de patogenicidade em Escherichia coli Enteroagregativas da microbiota intestinal de pacientes com doença inflamatória intestinal - Thomazini, Cristiane Melissa [UNESP] (2010)
Intestinal population of Escherichia coli is increased in patients suffering from inflammatory bowel disease (IBD), but the reason for this elevation and particular features of these bacteria are not fully known. In this study, the adherence abilities and phenotypes of a collection of 131 E. coli isolates cultured from rectal biopsies of 27 subjects diagnosed with ulcerative colitis (UC), 8 with Crohn’s disease (CD) and 19 control patients were investigated, using HEp-2 cells in assays of 3 and 6h of bacteria-cell contact. The isolates were also PCR screened for the presence of markers linked to adherence and invasion: plasmid of aggregative adhesion (pAA) and the aggregative adherence fimbriae R (aggR), E. coli attaching and effacing (eae), invasion-associated locus (ial) and invasion plasmid antigen H (ipaH) genes. Enteroagregative E. coli (EAEC) strains, as detected in 3h adherence assays, were found in 25/35 (71.4%) IBD patients and in 5/19 (26.3%) controls (P<0.02). None of the strains had ial or ipaH, and those from CD patients were also negative for other investigated markers. Three UC patients had strains harboring both pAA and aggR and another 4 UC patients had eae+ strains. The results of the present study showed that EAEC were the dominant E. coli group found in the colonic mucosa of IBD patients. In addition, the detection of virulence markers in strains from 7/27 UC (25,9%), but in none from CD patients (p<0.02) suggests the involvement of known potentially pathogenic (typical) EAEC with ulcerative colitis